Les miserables, volume two - Hugo, Victor. 1802-1885 (Everyman's Library, 1964)
Summary: Story of Valjean, the ex-convict who rises against all odds from galley slave to mayor, and the fanatical police inspector who dedicates his life to recapturing Valjean